THE INFLUENCE OF PERCEIVED ORGANIZATIONAL SUPPORT ON JOB SATISFACTION THROUGH MOTIVATION AND JOB STRESS AS INTERVENING VARIABLES: A CASE STUDY OF PONTIANAK POST. - admin, Febri Yunirman B12111007 (Jurnal Manajemen Update, 2017)
This research entitled â€œThe Influence of Perceived Organizational Support on Job Satisfaction through Motivation and Job Stress as Intervening Variables: A Case Study of Pontianak Postâ€. The problem in this research is how perceived organizational support can influence the job satisfaction of Pontianak Postâ€™s employees through motivation and job stress. The purpose of this study was to determine the description of perceived organizational support, motivation, job stress, and job satisfaction at Pontianak Post and analyse how much the influence of perceived organizational support on job satisfaction of Pontianak Postâ€™s employee trough motivation and job stress as intervening variables. The sample in this research was the all employees of Pontianak Post at editorial department. The measurement of this study is using a Likert scale and analysed by using SPSS 16 for the test of validity, reliability, classic assumption test, R square test and T test in order to analyse the relationship of all variables and path analysis to measure the direct and indirect relationship between independent and dependent variables. Based on the research result, it can be known that perceived organizational support had positive and significant indirect relationship on job satisfaction trough motivation and job stress as intervening variables. Keywords: Perceived Organizational Support, Motivation, Job Stress, Job Satisfaction Â